2014
DOI: 10.1177/000313481408000520
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Pilonidal Sinus Disease with Modified Primary Closure: New Technique on 450 Patients

Abstract: Chronic pilonidal disease is a debilitating condition that typically affects young adults. Controversy still exists regarding the best surgical technique for the treatment of pilonidal disease in terms of minimizing disease recurrence and patient discomfort. The present study analyzes the results of excision with our modified primary closure. This retrospective study involving consecutive patients with pilonidal disease was conducted over a 6-year period. From January 2004 to January 2010, 450 consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…at riskRR in % (95% CI)Nr. at riskPrimary open (1243)0 (0.0–0.0)12032.5* (1.2–3.8)441*4.5* (2.5–6.6)267*NANA 35, 56, 70, 72, 80, 91, 94– 96, 99, 100, 120, 610– 613 Primary median closure (5583)3.3 (2.8–3.8)41847.6 (6.7–8.5)193910.1* (8.8–11.4)786*12.2 (10.3–14.2)382 35, 56, 91, 94– 96, 99, 100, 129, 144, 146, 161, 162, 165– 168, 171, 179, 182, 186, 197, 205, 209, 214, 215, 218– 222, 610– 621 Primary asymmetric closure (1099)0.0* (0.0–0.0)1099*0.0* (0.0–0.0)1096*0.1* (0.0–0.2)1022*3.6* (2.4–4.8)937* 100, 129, 256, 260, 622 Karydakis/Bascom (109)3.7 (0.0–7.4)109NANANANANANA 16, 622 Limberg/Dufourmentel (944)0.0* (0.0–0.0)944*0.3* (0.0–0.7)891*0.3 (0.0–0.7)618NANA 56, 100, 165, 182, 205, 328, 334, 336…”
Section: Resultsmentioning
confidence: 99%
“…at riskRR in % (95% CI)Nr. at riskPrimary open (1243)0 (0.0–0.0)12032.5* (1.2–3.8)441*4.5* (2.5–6.6)267*NANA 35, 56, 70, 72, 80, 91, 94– 96, 99, 100, 120, 610– 613 Primary median closure (5583)3.3 (2.8–3.8)41847.6 (6.7–8.5)193910.1* (8.8–11.4)786*12.2 (10.3–14.2)382 35, 56, 91, 94– 96, 99, 100, 129, 144, 146, 161, 162, 165– 168, 171, 179, 182, 186, 197, 205, 209, 214, 215, 218– 222, 610– 621 Primary asymmetric closure (1099)0.0* (0.0–0.0)1099*0.0* (0.0–0.0)1096*0.1* (0.0–0.2)1022*3.6* (2.4–4.8)937* 100, 129, 256, 260, 622 Karydakis/Bascom (109)3.7 (0.0–7.4)109NANANANANANA 16, 622 Limberg/Dufourmentel (944)0.0* (0.0–0.0)944*0.3* (0.0–0.7)891*0.3 (0.0–0.7)618NANA 56, 100, 165, 182, 205, 328, 334, 336…”
Section: Resultsmentioning
confidence: 99%
“…Most studies with long-term follow-ups (5-15 years) reported increased rate of recurrence in all open and closed techniques. [23][24][25] A meta-analysis of older studies found 13% recurrence at 1 year after open excisions of PS, and 15% after closed excision. 26 A recent study found high recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Others have commented that some patients have an issue with the cosmetic appearance after Limberg flap [66], whereas the Karydakis operation had a cosmetic satisfaction rate of 91% in another study [67]. The cleft lift was described as having an excellent cosmetic result [33], as did a modified primary closure [68]. Studies should include the cosmetic appearance as a measure of success.…”
Section: Discussionmentioning
confidence: 99%